Entrepreneurial passion and professionalism on the success of SMEs in Plateau State, Nigeria - Yilkes Danladi Nson; Adejoh Solomon Abimaje (Journal of Sustainable Tourism and Entrepreneurship, 2024)
Purpose: This study examines the mediating influence of professionalism on the relationship between entrepreneurial passion and success in small and medium-sized enterprises (SMEs) in Nigeria. Research Methodology:  Data were collected from a sample size of 288 SMEs owners in Jos South LGA of Plateau State out of a total population of 1026 SME owners and were analyzed using PLS-SEM version 3.0. Results: The results of the direct relationships revealed a significant positive relationship between the variables HO1 (? = 0.831, tstat = 20.447, and p-value = 0.000), HO2 (? = 0.882, t-stat = 51.325, and p-value = 0.000), and HO3 (? = 0.168, t-stat = 3.822, and p-value = 0.000). Mediation analysis revealed that EP  and ES were mediated by professionalism (HO4, t-stat = 3.817, p = 0.000). Limitations: This study was limited to EP, ES, and professionalism, and was analyzed using PLS-SEM version 3.0. Contributions: This paper provides useful insights for aspiring entrepreneurs, managers, policy makers, corporate businesses, and governmental and nongovernmental organizations around the world to facilitate business success using passion and professionalism. Originality/Value: This study adds to the corpus of information on professionalism in entrepreneurship and small business literature in Africa, which academics in developing countries generally overlook.